Evolution of Subsurface Temperatures in West Sumatra - Southern Java Waters During 2010–2014 Indian Ocean Dipole Events - A.R. Khairun Nisa; Ivonne M. Radjawane (Jurnal Segara, 2021)
The temperature anomaly formation in the West Sumatra and South Java Waters plays an important role in the formation of the Indian Ocean Dipole (IOD). There have not been many detailed studies on the evolution of temperature anomalies in the subsurface layers in the area during the IOD events. In this study, temperature data from the HYCOM were used to examine the evolution of temperature anomalies on the surface and subsurface in the event of negative IOD (nIOD) 2010 and positive IOD (pIOD) 2012). The analysis was done using a cross-section plot and a Hovmöller diagram. It has shown that in the negative IOD 2010, a positive temperature anomaly in the subsurface layer was started four months earlier than the surface layer and ended six months after the IOD event. In contrast to positive IOD 2012, a negative temperature anomaly formed in the surface layer seven months earlier, and then move to the deeper layer coincide with the onset of the positive IOD event. The negative anomaly in both layers was simultaneously over two months after the positive IOD event over. The La-Niña phase that coincides with the positive or negative IOD event, influences the process of forming temperature anomalies in the subsurface layer, which in this case supports (inhibits) the formation of positive (negative) temperature anomalies in negative (positive) IOD event. The temperature anomaly in the subsurface layer can be an alternative indicator in identifying and predicting IOD events.